The impact of slip perturbations on minimum toe clearance during walking in younger and older adults - Aaron M. Gelinne; Andrew D. Shelton; Jason R. Franz (PLoS ONE, 2025)
Purpose The purpose of this study was to examine the kinematic differences in minimum toe clearance (MTC), a risk factor for falls, between older and younger adults during habitual walking and treadmill-induced slip perturbations. Materials and methods Data from 28 older adults and 30 younger adults were analyzed for this study. Each subject was fitted with whole-body retroreflective markers for 3D motion capture and walked habitually and while responding to treadmill-induced slip perturbations. Minimum toe clearance and leg joint kinematics were obtained and compared between groups and across conditions. Results There was no difference in MTC between age groups during habitual walking (Older: 5.75 ± 1.08 cm, Younger: 5.45 ± 0.93 cm, p = 0.125). Independent of age, MTC increased significantly in response to treadmill-induced slips (p < 0.001). However, significant age × condition interactions revealed that older adults increased MTC significantly less than younger adults in response to treadmill-induced slips. Older adults walked with significantly less knee flexion (31.4 ± 9.9° vs. 41.3 ± 11.9°; p < 0.001) and significantly more hip internal rotation (6.5 ± 6.3° vs. 3.8 ± 6.3°; p = 0.004) than younger adults during slip perturbations. Conclusions This study builds on prior work to conclude that, compared to younger adults, older adults appear to have a diminished capacity to instinctively increase MTC during walking in response to slip-like balance perturbations, which may allow them lesser time to accommodate instability.